2000
DOI: 10.1021/jm000346k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, SARs, and Pharmacological Characterization of 2-Amino-3 or 6-fluorobicyclo[3.1.0]hexane-2,6-dicarboxylic Acid Derivatives as Potent, Selective, and Orally Active Group II Metabotropic Glutamate Receptor Agonists

Abstract: (+)-2-aminobicyclo[3.1.0]hexane-2,6-dicarboxylic acid (4, LY354740), a highly selective and orally active group II metabotropic glutamate receptor (mGluR) agonist, has increased interest in the study of group II mGluRs. Our interest focused on a conformationally constrained form of compound 4, because it appeared that the rigid form resulted in not only selectivity for group II mGluR but was orally active. Therefore, we introduced a fluorine atom to compound 4, based on the molecular size (close resemblance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
106
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 55 publications
2
106
0
Order By: Relevance
“…Finally, eliminating the phenylsulfinyl group of (Ϯ)-12 under neutral conditions in benzene yielded vinyl fluoride (Ϯ)-6a (34% yield). Fluorination of (Ϯ)-11 with NFSI proceeded at low temperatures in comparison to the method reported with KF · HF, 13) a nucleophilic fluorination reagent, giving (Ϯ)-6a as the sole product without elaborate separation by column chromatography.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Finally, eliminating the phenylsulfinyl group of (Ϯ)-12 under neutral conditions in benzene yielded vinyl fluoride (Ϯ)-6a (34% yield). Fluorination of (Ϯ)-11 with NFSI proceeded at low temperatures in comparison to the method reported with KF · HF, 13) a nucleophilic fluorination reagent, giving (Ϯ)-6a as the sole product without elaborate separation by column chromatography.…”
Section: Resultsmentioning
confidence: 97%
“…20) We have already reported that (ϩ)-(1S,2S,3S,5R,6S)-2-amino-3-fluorobicyclo[3.1.0]hexane-2,6-dicarboxylic acid (ϩ)-1 (MGS0008) was a potent and selective group II mGluR agonist. 13) Compound (Ϯ)-1 exhibited approximately 70-fold higher agonist activity than its diastereomer (Ϯ)-2 and (ϩ)-1 is approximately 90-fold as active as its enantiomer (Ϫ)-1 ( Fig. 1).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…First, there have been reported a few potent leads having a chiral fluorine-containing structure, such as fluorothalidomide, fluorodonepezil, etc. [6][7][8][9] These compounds were found to be pharmacologically more effective than the fluorine-free parent compounds. This suggests that the screening of biological activities of chiral fluorine-containing acids 1 could guide the development of new kinds of medicinal agents.…”
mentioning
confidence: 99%